The Influence of Immigration and Foreign Workers on Croatia’s Employment Market - Mladen Rajko; Ivica Zdrilić; Monika Hordov (World, 2025)
This study systematically examines the impact of immigration, emigration, and the influx of foreign workers on employment, unemployment, and economic growth in the Republic of Croatia. The primary objective of the research is to understand how these demographic and economic changes shape the labor market and evaluate their long-term effects on gross domestic product (GDP) and wage levels. The methodology used in this study involves a comprehensive analysis of macroeconomic data from Croatia over the past 11 years, focusing on critical indicators such as employment, unemployment, immigration, emigration, foreign workers, wages, and GDP trends. This approach provides valuable insights into how migration patterns influence critical labor market indicators. The findings reveal that immigration and foreign workers significantly impact employment, particularly in stabilizing sectors like tourism and construction. Additionally, a positive correlation was found between the number of foreign workers and GDP growth. In conclusion, the research underscores the importance of immigration and foreign workers in addressing labor shortages and driving economic growth in Croatia. However, targeted policies are needed to ensure the successful integration of foreign workers and the long-term sustainability of the domestic labor market.